2000
DOI: 10.1103/physreve.61.7239
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition ofn-alkane layers adsorbed on mica

Abstract: Thin (thickness h approximately 3 nm) films of n-octadecane and n-hexadecane adsorbed on mica surfaces from vapor close to their bulk melting points (T(m)) have been studied in a surface force apparatus. Using data on the growth rate of capillary condensates between the mica surfaces in contact and measurements of h, we have identified a transition in the structure of the adsorbed films a few degrees above T(m). As T decreases the alkane layers appear to undergo a transition to a more ordered structure, akin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…This feature did not allow accurate measurements of their refractive index profiles, and, therefore, we concentrated here instead on the mean refractive index of the n-hexadecane bridges. This effect may be related to the large difference in the rates of evaporation of the two liquids (12)(13)(14)(15). Second, the much slower rates of evaporation and condensation of n-hexadecane allowed for more accurate measurements to be made, especially during the final stages of evaporation, than was previously possible with cyclohexane.…”
Section: Resultsmentioning
confidence: 99%
“…This feature did not allow accurate measurements of their refractive index profiles, and, therefore, we concentrated here instead on the mean refractive index of the n-hexadecane bridges. This effect may be related to the large difference in the rates of evaporation of the two liquids (12)(13)(14)(15). Second, the much slower rates of evaporation and condensation of n-hexadecane allowed for more accurate measurements to be made, especially during the final stages of evaporation, than was previously possible with cyclohexane.…”
Section: Resultsmentioning
confidence: 99%
“…1,5,6 Although rotator phases have been studied in bulk crystals of alkanes, there are few reports of these phases in molecularly thin films. [7][8][9][10][11]16 Solid C32 films grown on SiO 2 surfaces have been found to follow the Stranski-Krastanov growth mode. At the substrate-alkane interface, there is a complete bilayer of molecules with their long axis parallel to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Between T m and T s the surface of liquid n-octadecane is more ordered than the bulk (the surface entropy is negative) and consists of a monomolecular layer of parallel molecules essentially perpendicular to the interface. A similar surface phase transition also occurs with n-octadecane (and other long-chain n-alkanes adsorbed from vapor on mica), [16,17] and this changes the wetting properties of the surface. Above T s the adsorbed layer is disordered, and the surface is a mixture of methyl and methylene groups.…”
Section: Freezing and Melting Of Capillary Condensates Of N-octadecanementioning
confidence: 82%
“…Studies of the initial growth rate of capillary condensates of n-octadecane as well as measurements the adsorbed layer thickness have shown that the adsorbed film undergoes a structural transition about 28C above the melting point. [16,17] As this temperature T s is approached from above, the layer thickens and becomes more ordered. This transition is akin to the surface freezing transition found at the liquid-vapor interface of n-octadecane (and other long-chain n-alkanes [18] ).…”
Section: Freezing and Melting Of Capillary Condensates Of N-octadecanementioning
confidence: 98%
See 1 more Smart Citation